Genomic and prognostic heterogeneity among RAS/BRAFV600E/TP53 co‐mutated resectable colorectal liver metastases. Issue 4 (8th January 2021) - Berg, Kaja C. G.; Brunsell, Tuva H.; Sveen, Anita; Alagaratnam, Sharmini; Bjørnslett, Merete; Hektoen, Merete; Brudvik, Kristoffer W.; Røsok, Bård I.; Bjørnbeth, Bjørn Atle; Nesbakken, Arild; Lothe, Ragnhild A.
Abstract : Hepatic resection is potentially curative for patients with colorectal liver metastases, but the treatment benefit varies. KRAS / NRAS ( RAS) / TP53 co‐mutations are associated with a poor prognosis after resection, but there is large variation in patient outcome within the mutation groups, and genetic testing is currently not used to evaluate benefit from surgery. We have investigated the potential for improved prognostic stratification by combined biomarker analysis with DNA copy number aberrations (CNAs), and taking tumor heterogeneity into account. We determined the mutation status of RAS, BRAF V600, and TP53 in 441 liver lesions from 171 patients treated by partial hepatectomy for metastatic colorectal cancer. CNAs were profiled in 232 tumors from 67 of the patients. Mutations and high‐level amplifications of cancer‐critical genes, the latter including ERBB2 and EGFR, were predominantly homogeneous within patients. RAS / BRAF V600E and TP53 co‐mutations were associated with a poor patient outcome (hazard ratio, HR, 3.9, 95% confidence interval, CI, 1.3–11.1, P = 0.012) in multivariable analyses with clinicopathological variables. The genome‐wide CNA burden and intrapatient intermetastatic CNA heterogeneity varied within the mutation groups, and the CNA burden had prognostic associations in univariable analysis. Combined prognostic analyses of RAS / BRAF V600E / TP53 mutations and CNAs, either as a high CNA burden or high intermetastatic CNA heterogeneity, identified patients with a particularly poor outcome (co‐mutation/high CNA burden: HR 2.7, 95% CI 1.2–5.9, P = 0.013; co‐mutation/high CNA heterogeneity: HR 2.5, 95% CI 1.1–5.6, P = 0.022). In conclusion, DNA copy number profiling identified genomic and prognostic heterogeneity among patients with resectable colorectal liver metastases with co‐mutated RAS / BRAF V600E / TP53 . Abstract : Colorectal cancer commonly metastasizes into multiple liver foci, but intermetastatic heterogeneity remains poorly described. Here, we demonstrate that mutations of RAS/BRAF/TP53 are homogeneous within patients, while DNA copy number aberrations can vary greatly. RAS/BRAF/TP53 co‐mutations conferred a dismal prognosis, and co‐mutations combined with a high burden and heterogeneity of copy number aberrations identified patients with the poorest outcome.